Chapter 2 - Chemical Composition and Structure: Linear Algebra - Constales, Denis; Yablonsky, Gregory S.; D'Hooge, Dagmar R.; Thybaut, Joris W.; Marin, Guy B.
Given a set of components of known atomic composition, establish which of them are key to determine, together with the element balances, the amounts of all others. Furthermore, find a way of generating all possible reactions involving these components.
Keywords: CHEMICAL COMPOSITION; STRUCTURE; LINEAR ALGEBRA